STUDENTS’ ENTHUSIASM IN SPEAKING CLASS DURING ONLINE LEARNING - Sirait, Ria valentina; Regina, Regina; Riyanti, Dwi (﻿Kantor Bahasa Provinsi Bangka Belitung, 2023)
This research aimed to find how strong students' enthusiasm is in speaking class during online learning. The research design in this study was descriptive with a quantitative approach. The population in this research were all the students of English education study program, and the sample of this study was English education study program, morning class, batch 2020 of Universitas Tanjungpura consisting of 37 students. From the 37 students, the researcher took 3 students to get interviewed. These three students have been selected based on their low, average and high questionnaire results. The research instruments were a questionnaire and interview, meanwhile the data analysis used a percentage formula. This research showed that most students are enthusiastic about online learning. Based on the questionnaire results processed using Ms. Excel. The result showed that 71% of students are enthusiastic in speaking class during online learning, and it is categorized as high, referring to the benchmark category by Purwanto (2010). Derived from the interview results, the students mentioned that their enthusiasm depends on internal and external factors that occur during online learning. The internal factors include boredom, lack of sources, and lack of interaction. However, the external factors discovered are lagging, inadequate tools, and unstable signals. In addition, the lecturer also plays a crucial role in making the classroom environment as joyful as it should be. An example of a fun class can be seen from the students being active in the class as well as the good relationship between the students and the lecturer. A cheerful situation will increase students' enthusiasm for learning.